Sistem Informasi Geografis Mencari Rute Terpendek Pada Pemetaan SMP di Kecamatan Mustikajaya Dengan Algoritma A-Star A(*) Berbasis Web - Novandra , Deka Darma; Putra , Tri Dharma; Mayadi , Mayadi (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Many parents have few references to send their children to school, and are only based on suggestions or invitations from those closest to them. Lack of information can be one of the reasons for the lack of references for parents to choose a junior high school for their child. The lack of information regarding the location of junior high schools is the reason for the lack of references for parents to send their children to school. Based on the existing problems, the authors propose a web-based geographic information system that uses the A-Star Algorithm (A*) to be used as a means of information and also to add references for parents/guardians. The A-Star (A*) algorithm is a method for searching for information about the distance to reach a destination by selecting the closest route.